Moçambique Para Todos (?) Mozambique and Political Violence The Opinions of the Opposition Youth (Altre Modernità, 2016)
This paper draws inspiration from a case of political violence in Mozambique to present the results of a six-month fieldwork research in the Mozambican capital city Maputo. The research targets were the members of the youth leagues affiliated to the two main opposition parties, Renamo and MDM. Specifically, the author investigated the motivations of these youths to participate in the political opposition despite the peril of political violence. Following an essential résumé of the histories of the assessed youth leagues, the author provides the drivers behind his decision to analyze such topics. Through the different types of violence as defined by Johan Galtung, the author argues that the present case study might be a degeneration of cultural political violence, embedded in the history of Mozambique since the years of its independence. In the present day, such violence has been threatening more and more directly an already fragile democracy. Moreover, since the present case study revolves around opinions of youths, the assessed theoretical framework includes studies violence in general and a particularly intriguing assessment of the present condition of youths in Mozambique and, even more specifically, in its capital city, Maputo. Successively, the author summarizes the emerging of structural political violence in post-independence Mozambique. As it concerns the main corpus of the research, the author used a qualitative methodology that combines a historical and ethnographic approach. The findings reveal that the interviewed members of the considered youth leagues have an idea of political violence, which goes beyond the mere politics. Further, they demonstrated a quite straightforward consideration on the reasons why a lingering political violence is still present in Mozambique. Further, the interviewees also expressed their own point of view on the consequences of such political violence on themselves and on Mozambican youth in general. Although the findings also aimed to surface any possible discrepancies between the answers of male and female interviewees, they all unilaterally blamed the ruling Frelimo party for the ongoing tension with few differences in their answers.